Effect of Soil Stiffness on the Design Parameters of Stiffened Raft Foundation on a Highly Expansive Soil (University of Khartoum Engineering Journal, 2022)
This paper evaluates the effect of soil stiffness on the design parameters of a stiffened raft on an expansive soil of high potential for swelling. The evaluation was based on a finite element program originally developed by Wray [8]. The input soil parameters were measured in the laboratory for a highly expansive soil from Central Sudan. Soil Young’s Modulus was measured at varying moisture conditions using the unconfined compression test. The effects of soil modulus on moments, shear forces and differential deflection were investigated for a case study of a light residential building founded on the tested soil. Evaluation was made using different values of measured and assumed heave and end penetration. Results showed that the modulus of elasticity decreased as water content of the soil increased. The determined results of the finite element program suggested that, generally, the magnitude of longitudinal, traverse moments, shear forces, and differential deflection increased with increase in the soil modulus of elasticity and that the heave values affected the results.